1991
DOI: 10.1055/s-2006-960081
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Genotoxic Properties of Essential Oils withBacillus subtilis rec-Assay andSalmonella/Microsome Reversion Assay

Abstract: Genotoxic properties of essential oils from Anthemis nobilis L., Artemisia dracunculus L., Salvia officinalis L., Salvia sclarea L., Satureja hortensis L., Satureja montana L., Thymus capitatus L., Thymus citriodorus Schreb., Thymus vulgaris L., Citrus bergamia Risso, were studied with Bacillus subtilis rec-assay and Salmonella/microsome reversion assay. The essential oil of Artemisia dracunculus L. "Piemontese" turned out to be active in the rec-assay but not in the Salmonella test. DNA-damaging activity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(41 citation statements)
references
References 6 publications
3
35
0
3
Order By: Relevance
“…sativum, A. absinthium, C. regalis, C. carvi, I. helenium, J. regia, S. hortensis, and V. officinalis showed the best activity against the infective third-stage larvae of T. colubriformis in the LMI test, and a significant anthelmintic effect on egg embryogenesis (A. suum) was demonstrated by extracts from A. sativum, A. absinthium, C. carvi, D. carota, and J. regia. In summary, based on the results of the above-described experiments and literature data indicating low levels of toxicity for extracts from A. sativum (Saxena et al, 2005;Velasco-Velázquez et al, 2006), A. absinthium (Chiasson et al, 2001;Muto et al, 2003), C. carvi (Kumar & Singh, 2006), I. helenium (Spiridonov et al, 2005;Dorn et al, 2006), J. regia (Inbaraj & Chignell, 2004;Bhatia et al, 2006), S. hortensis (Zani et al, 1991), and V. officinalis (Romero-Jimenez et al, 2005;Yao et al, 2007), we suggest that some of these plant materials could be prospective sources for development of new antiparasitical herbal remedies. However, further phytochemical studies are required to determine the types of compounds responsible for the anthelmintic properties of these species.…”
Section: Discussionmentioning
confidence: 54%
“…sativum, A. absinthium, C. regalis, C. carvi, I. helenium, J. regia, S. hortensis, and V. officinalis showed the best activity against the infective third-stage larvae of T. colubriformis in the LMI test, and a significant anthelmintic effect on egg embryogenesis (A. suum) was demonstrated by extracts from A. sativum, A. absinthium, C. carvi, D. carota, and J. regia. In summary, based on the results of the above-described experiments and literature data indicating low levels of toxicity for extracts from A. sativum (Saxena et al, 2005;Velasco-Velázquez et al, 2006), A. absinthium (Chiasson et al, 2001;Muto et al, 2003), C. carvi (Kumar & Singh, 2006), I. helenium (Spiridonov et al, 2005;Dorn et al, 2006), J. regia (Inbaraj & Chignell, 2004;Bhatia et al, 2006), S. hortensis (Zani et al, 1991), and V. officinalis (Romero-Jimenez et al, 2005;Yao et al, 2007), we suggest that some of these plant materials could be prospective sources for development of new antiparasitical herbal remedies. However, further phytochemical studies are required to determine the types of compounds responsible for the anthelmintic properties of these species.…”
Section: Discussionmentioning
confidence: 54%
“…Several studies with various essential oils or their main components have demonstrated that, generally, most of them did not induce nuclear mutations (Bakkali et al 2008). However, some exceptions should be identified, such as Artemisia dracunculus oil (Zani et al 1991), Mentha spicata oil (Karpouhtsis et al 1998), Anethum graveolens oil and Pinus sylvestris oil (Lazutka et al 2001). In the present study, the MNPCE frequency of C. guianensis oil treated groups was very similar to negative control, suggesting that C. guianensis oil show no genotoxic activity for all doses tested (250, 500, and 1.000 mg/kg bw).…”
Section: Discussionmentioning
confidence: 99%
“…Genotoxic properties of the essential oils of S. hortensis and S. montana were studied with Bacillus subtilis rec-assay and Salmonella/microsome reversion assay by Zani et al (1991). Both oils exhibited moderate activity in rec-assay and Salmonella tests.…”
Section: Genotoxic Activitymentioning
confidence: 99%